Flexible Hardware-Based Stereo Matching. (18th January 2009) - Ambrosch, Kristian; Kubinger, Wilfried; Humenberger, Martin; Steininger, Andreas
Abstract : To enable adaptive stereo vision for hardware-based embedded stereo vision systems, we propose a novel technique for implementing a flexible block size, disparity range, and frame rate. By reusing existing resources of a static architecture, rather than dynamic reconfiguration, our technique is compatible with application specific integrated circuit (ASIC) as well as field programmable gate array (FPGA) implementations. We present the corresponding block diagrams and their implementation in our hardware-based stereo matching architecture. Furthermore, we show the impact of flexible stereo matching on the generated disparity maps for the sum of absolute differences (SADs), rank, and census transform algorithms. Finally, we discuss the resource usage and achievable performance when synthesized for an Altera Stratix II FPGA.